STRATEGI KOMUNIKASI RADIO UKIM FM MELALUI MEDIA SOSIAL DALAM MENGGAET PENDENGAR - Trientje Marlein Tamtelahitu (Universitas Tidar, 2020)
Abstract: of Maluku Maluku UKIM), which must develop itself so that its presence is still considered by the community and able to hook the entire community of the UKIM FM radio community because researchers realize that UKIM FM radio has not been accessed in full by the entire community of the UKIM FM community. The purpose of this study is to be able to describe the UKIM FM radio communication strategy through social media in attracting listeners . This research uses descriptive qualitative research methods. The results showed that the strategy implemented in the program was not a random strategy but with Susan Tyler Eastman's criteria. Compliance Strategy (compability), Events and Programs broadcast to coincide with the time of student activities and respond to the needs of citizens. In general, the program can be said to be successful in attracting listeners through social media because it is able to meet the needs of citizens by presenting programs that are of interest to residents. That success can be achieved from a strategy to attract listeners through Social media.Key words: Communication Strategy, Broadcasting Strategy, Radio, Social Media, Listener